Enhancing Flood Disaster Resilience in Early Childhood Education through Interactive Learning: A Case at TKIU Birrul Walidain Plupuh Sragen, Indonesia - Kencono, Dewi Sekar; Rahmatullah, Azam Syukur; Astuti, Pinta; Mutmainah, Nur Fitri; Agustiyara, Agustiyara (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
Indonesia's geographical location renders it highly susceptible to natural disasters, including frequent flooding along major river basins like the Bengawan Solo. Young children are particularly vulnerable during such events, yet disaster risk reduction (DRR) education tailored for early childhood settings remains underdeveloped.This qualitative case study describes the implementation and perceived effectiveness of an interactive, play-based DRR education program on flood preparedness for preschoolers at TKIU Birrul Walidain Muhammadiyah Plupuh, Sragen, near the Bengawan Solo River.  Over three months, the program used evacuation scenarios, educational games, and creative storytelling.  Participants observed and analyzed program documentation, including activity reports and photos.  Engaging young children in interactive learning about flood hazards, warning signals, and safe evacuation techniques was beneficial.  The activities raised children's awareness and enthusiasm.  The study suggests including age-appropriate, interactive DRR teaching into early childhood curriculum to build resilience.  It supports research indicating even young children can participate in DRR activities, making places safer (Proulx & Aboud, 2019).  DRR should be integrated into preschool curricula and longitudinal research should be done to examine long-term effects